(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
Rail transportation being the economic means of transportation, the majority of pedestrians rely on them in countries like India. Unlike metro stations, in intercity railway stations exists a wide degree of heterogeneity in pedestrian traffic. Pedestrians walking speed on stairways depends on various factors grouped under pedestrian, infrastructure, and environmental characteristics. Understating pedestrian perception of quality of service on existing facilities provides the planners to incorporate pedestrian bothered factors for comfortable access in the design. In this research work, pedestrian perceived level of service on six different stairways in intercity railway stations was analyzed. The questionnaire survey was adopted to understand the individual pedestrian perception towards the level of service on each stairway. Pedestrian characteristics such as age, education qualification, preference of usage between stairway and escalator, and stairway characteristics such as width, inclination, and side friction significantly affect individual’s perception of the serviceability of a stairway. A regression model was also developed by considering the significant factors affecting the pedestrian's perceived level of service of the stairway. Results of this study help in evaluating a stairway facility and arrive at better planning, design, and management to increase its efficiency. This study also helps in making design policies and guidelines for new stairways for better accessibility.